2019
DOI: 10.21203/rs.2.12038/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Antifungal Susceptibility of Candida albicans Causing Vaginal discharge Among Pregnant Women in Lebanon

Abstract: Background: Vaginal candidiasis is frequently prevalent in pregnant women and is associated with sepsis and adverse neonatal outcomes. This study determined the presence of Candida species in symptomatic pregnant women and evaluated the antifungal susceptibility profile of the isolated strains. It also aimed to explore whether Candida species predicts gestational complications and adverse neonatal outcomes. Methods: A total of 258 pregnant women at 35 to 37 week of gestation participated in this study. Vaginal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
4
4
1
Order By: Relevance
“…A statistically significant association between diabetes and the rate of VVC during pregnancy had been found in a study by Masri et al [39] which follows the result found by Kanagal [40]. C. albicans was found to be significantly associated with gestational diabetes [33]. Nevertheless, several studies did not find any significant statistical relationship between diabetes and VVC during pregnancy [29,36,43].…”
Section: Diabetes Mellitussupporting
confidence: 54%
See 1 more Smart Citation
“…A statistically significant association between diabetes and the rate of VVC during pregnancy had been found in a study by Masri et al [39] which follows the result found by Kanagal [40]. C. albicans was found to be significantly associated with gestational diabetes [33]. Nevertheless, several studies did not find any significant statistical relationship between diabetes and VVC during pregnancy [29,36,43].…”
Section: Diabetes Mellitussupporting
confidence: 54%
“…Waikhom et al [27] found the highest cumulative prevalence of NAC spp., 74.1%, where C. glabrata alone accounted for 57.4% of prevalence among pregnant women in Ho municipality, Ghana. Ghaddar et al [33] and Sangaré et al [25] also found 58% and 59.61% prevalence of NAC spp., respectively. Another study by Ghaddar et al is where 56.6% (C. glabrata 44.5%) prevalence of NAC spp.…”
Section: Prevalence Of Different Species Of Candida Amongmentioning
confidence: 90%
“…and 95% were susceptible to Voriconazole and 5% were resistant. Our findings agree with Ghaddar et al [28] who detected nearly similar results. Furthermore, Zeng et al reported a total of 18.6% of the candida isolates were resistant to fluconazole.…”
Section: Discussionsupporting
confidence: 94%
“…albicans in the GDM group. Similar to our study, Ghaddar et al 25 also found an increased prevalence of NCAC and an association of C . albicans with GDM.…”
Section: Discussionsupporting
confidence: 92%